Francisella novicida can utilize Paramecium bursaria as its potential host. Issue 1 (29th November 2021) - Watanabe, Kenta; Motonaga, Akane; Tachibana, Masato; Shimizu, Takashi; Watarai, Masahisa
Summary: Francisella novicida is a facultative intracellular pathogen and the causative agent of tularemia. Although cases of infection caused by exposure to contaminated water have been reported, its natural host and ecology in the environment remain unclear. In this study, we investigated in vitro the possibility that Paramecium bursaria may be a useful tool as a protist host model of F. novicida . Experimental infection with F. novicida resulted in a stable intracellular relationship within P. bursaria . This symbiotic intracellular relationship was not observed in experimental infections with other Francisella species and Legionella pneumophila . We found that F. novicida showed similar behaviour to that of the eukaryotic endosymbiont of P. bursaria, the green algae Chlorella, in the internalization process. In addition, stable intracellular localization of F. novicida was possible only when Chlorella was not present. Although we investigated the type VI secretion system of F. novicida as a candidate for the bacterial factor, we found that it was not involved in the establishment of an intracellular relationship with P. bursaria . These results suggested that P. bursaria is potentially a protist host model for F. novicida and may be a useful tool for understanding the relationship between protist hosts and their symbionts.